Risk factors associated with caries and periodontal disease in a Center of Special Basic Education in Huánuco, 2017 - Basilio-Bernardo, Yulith (2020)
Objectives: To identify the risk factors associated with caries and periodontal disease in children from 7to18 years of age in the Center of Special Basic Education “Niño Jesús de Praga” in Huánuco 2017. Materials and methods: Observational, Analytical Design of cases and controls. A survey-type collection sheet was used. The sample was constituted of 60 special children (study group) and 60 non-special children (control group). Dependent variable: caries and periodontal disease (because they are the most frequent disease in the oral cavity). Independent variables: oral hygiene index, labor time, complication during pregnancy, salivary pH, carbohydrate intake and type of labor. Results: Among the risk factors for caries and periodontal disease, there is no statistically significant difference (p <0.05) with the labor time, nor the other factors. The following factors were determined as risk factors for caries: Oral hygiene index, labor time and complications during the pregnancy; and risk factors for periodontal disease: salivary pH, carbohydrate intake and type of labor. Furthermore, no significant differences (p> 0.05) were found between the DMFT+ dft index for caries (p: 0.36) and the CPITN index for periodontal disease (p: 0.89) for both groups. Conclusions: We found a significant difference between labor time and caries and periodontal disease that affect both groups. The risk factors were found specifically for caries and periodontal disease that are not as widely used for these oral diseases in both groups and no significant difference was found between the used indexes.